Current Trends in Blood Flow Restriction - Cuffe, Molly; Novak, Joel; Saithna, Adnan; Strohmeyer, H. Scott; Slaven, Emily (Frontiers in Physiology, 2022)
Purpose: The purpose of the study was to explore how individuals in the United States of America applied BFR/KAATSU devices and administered BFR/KAATSU training. In addition, the study sought to examine safety topics related to BFR/KAATSU training. Methods: The study was completed using survey research. Subjects were recruited through Facebook, email, and word of mouth. The survey was developed, piloted, and finally deployed March 22, 2021-April 21, 2021. Results: In total, 148 consented to the research; 108 completed the survey, and of those 108, 70 indicated current use with BFR/KAATSU equipment. Professions represented included athletic training, personal training, physical therapy, and strength and conditioning. The most common devices used were inflatable devices (n=43, 61.4%). Education completed prior to device administration was formal (n= 39, 55.7%) and/or self-directed (n=37, 52.9%). Barriers were faced by 29 (41.4%) when trying to enact training. Techniques and parameters varied during application. Screening processes were used (n=50, 71.4%) prior to training. The devices were used to determine restrictive pressure (n=31, 44.3%), and a supine position was used most when determining initial restrictive pressure (n=33, 47.1%). For subsequent restrictive pressure measurements, respondents repeated the same method used initially (n=38, 54.3%). Workload was often defined as the length of time under tension/load (n=22, 31.4%) and exercise was directly supervised (n=52, 74.3%). Adverse effects included bruising, lightheadedness, and cramping (n=15, 21.4%). The devices have also been applied on those with pathology (n=16, 22.9%). Conclusions: Those using blood flow restriction/KAATSU devices came from several professions and used an assortment of devices for BFR/KAATSU training. Individuals applied devices using a variety of parameters on populations for which efficacy has and has not been well defined.